The impact of combined administration of ropivacaine and dexamethasone on postoperative analgesia in perianal surgery with pudendal nerve block under ultrasound guidance: a prospective randomized controlled study - Yang, Tao-Ran; Pu, Dan; Cheng, Yan; Fan, Cheng-Xi; Hu, Ya-Jun; Wang, Ru-Rong; Li, Xue-Han (Frontiers in Pharmacology, 2024)
Background: In recent years, severe pain after perianal surgery has seriously affected the prognosis of hospitalized patients. How to maximize the improvement of postoperative pain and perioperative comfort becomes particularly important. Methods: This study was a double-blind randomized controlled trial (Registration No.: ChiCTR2100048760, Registration Date: July 16, 2021, Link: www.chictr.org.cn/showproj.html?proj=130226), and patients were randomly divided into two groups: one group underwent postoperative 20ml bilateral pudendal nerve block with 0.5% ropivacaine (P group), and the other group underwent postoperative 20ml bilateral pudendal nerve block with 0.5% ropivacaine + 8mg dexamethasone (PD group). The primary outcome was the incidence of moderate to severe pain at the first postoperative dressing change. Secondary outcomes included Quality of recovery-15 (QoR-15) score at 3 days after surgery, sleep quality, pain score at 3 days after surgery, and incidence of adverse events. Results: In the main outcome indicators, the incidence was 41.7% in the P group and 24.2% in the PD group (P = 0.01). The QoR-15 score and sleep quality in PD group were better than those in P group 2 days before surgery. The incidence of postoperative urinary retention was significantly decreased in PD group (P = 0.01). Conclusions: Local anesthesia with dexamethasone combined with pudendal nerve block (PNB) after perianal surgery can reduce the incidence of moderate to severe pain during the first dressing change. This may be one of the approaches to multimodal analgesia after perianal surgery.